A submillimeter frequency multiplier. Part 2. Substantiation of a long-lived compact bunch model - Mil’cho, M.; Ilyenko, K. (Radiofizika i èlektronika, 2020)
Subject and Purpose. Part 1 of the present paper presents a feasibility study of a submillimeter frequency multiplier based on a clinotron with a single slow-wave structure. The aim of Part 2 is to gain a better insight into the electron bunching mechanism, seeking for efficient energy exchange between the electron bunches and the RF field in the multiplier of the sort. Methods and Methodology. The research method is a theoretical analysis given to the electron bunching process in a BWO-type oscillator with rigorous numerical models involved. The bunch longitudinal size is calculated in steady state regime with regard to the space charge influence. The necessary conditions for compact electron bunching are sought via numerical integration of the motion equations of electrons subject to the interaction with the RF field of the slow-wave structure. Results. A mechanism of compact electron bunching has been revealed by numerical modeling and described. The pattern of long-lived compact electron bunches continuously moving along the surface of the clinotron comb-type slow-wave structure holds owing to the continuous deposition of compact electron bunches on the comb surface. The compact bunches are formed in electron beam layers farthest from the comb surface but moving to it in consequence of the electron beam inclination under magnetic field action (the clinotron effect). The bunch size and its dependence on the problem parameters have been specified. The research results find use in analysis of operational regimes of conventional clinotrons. Clinotron designers are provided with relevant recommendations. Conclusion. A model of electron bunching in clinotron-type oscillators has been developed with regard to the process of deposition of electron beam layers on the comb-type slow-wave structure surface. It is the existence of a system of compact electron bunches continuously moving along the comb surface that makes possible efficient electron beam interaction with the high-frequency electromagnetic field of multiplied-mode oscillations. We justifiably claim that multipliers of the kind can be advanced to the short-wave end of the submillimeter band.